2014
DOI: 10.1016/j.immuni.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular B30.2 Domain of Butyrophilin 3A1 Binds Phosphoantigens to Mediate Activation of Human Vγ9Vδ2 T Cells

Abstract: Summary In humans, Vγ9Vδ2 T cells detect tumor cells and microbial infections including Mycobacterium tuberculosis through recognition of small pyrophosphate containing organic molecules known as phosphoantigens (pAgs). Key to pAg-mediated activation of Vγ9Vδ2 T cells is the butyrophilin 3A1 (BTN3A1) protein that contains an intracellular B30.2 domain critical to pAg reactivity. Here, we have demonstrated through structural, biophysical and functional approaches that the intracellular B30.2 domain of BTN3A1 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
534
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(587 citation statements)
references
References 41 publications
35
534
2
Order By: Relevance
“…However, only the B30.2 domain of the BTN3A1 isoform can bind pAg 21 through a positively charged pocket. 22,23 This intracellular binding induced extracellular conformational changes of BTN3A, similar to those observed with 20.1 mAb and resulting Vg9Vd2 T cell activation. 24 Together, these data open new perspectives in Vg9Vd2 T cells-based immunotherapies, with BTN3A appearing as an interesting target to regulate their functions.…”
Section: Introductionsupporting
confidence: 51%
“…However, only the B30.2 domain of the BTN3A1 isoform can bind pAg 21 through a positively charged pocket. 22,23 This intracellular binding induced extracellular conformational changes of BTN3A, similar to those observed with 20.1 mAb and resulting Vg9Vd2 T cell activation. 24 Together, these data open new perspectives in Vg9Vd2 T cells-based immunotherapies, with BTN3A appearing as an interesting target to regulate their functions.…”
Section: Introductionsupporting
confidence: 51%
“…To identify those human chromosome(s) mandatory for PAg presentation, hybrid cells were cloned and tested for induction of reporter cell stimulation in the presence of 1 nM HMBPP. PCR karyotyping showed that loss of human chromosomes 2,3,7,8,9,10,11,13,17,18,20,21, and X had no effect on PAg-mediated activation of the reporter cells, while cells without Chr6 failed to induce activation of the reporter cells in the presence of HMBPP or zoledronate. For reasons so far unknown, 2 of 6 of the Chr6-bearing hybridoma cell lines stimulate the reporter cells in the presence of HMBPP and zoledronate but not in the presence of 2 mM sec-butylamine.…”
Section: Resultsmentioning
confidence: 99%
“…Given that BTN3A1 protein loaded with PAg in a cell-free system binds to recombinant Vγ9Vδ2 TCRs [12], we would predict that the missing Chr6-encoded gene(s) relate to cellular functions such as PAg loading of the BTN3A1 molecule or control of its cellsurface distribution or cellular compartmentalization, for which the PAg-binding intracellular B30.2 domain of BTN3A1 might be crucial [8][9][10][11][12]. The colocalization of BTN3 with genes associated with antigen-presenting function might be by coincidence, but is clearly reminiscent of what is seen for peptide-presenting MHC molecules [15].…”
Section: Discussionmentioning
confidence: 99%
“…The recent landmark discovery of butyrophilin 3A (BTN3A/ CD277) as the long-sought unconventional 'presenting' molecule for HMB-PP and IPP provided a molecular mechanism that elegantly integrates the action of endogenous and exogenous stimuli via binding of phosphoantigens to the intracellular B30.2 (PRY-SPRY) domain of BTN3A [22][23][24][25]. This intracellular recognition of HMB-PP and IPP evokes similar cases of B30.2-mediated innate responses through proteins such as TRIM5a and TRIM21 [26,27], thereby adding BTN3A to the rapidly growing number of innate pattern recognition receptors.…”
Section: Innate-like Pattern Recognition By Human Vc9/vd2 T Cellsmentioning
confidence: 99%
“…Overproduction of the low bioactivity compounds IPP and DMAPP as a result of a dysregulation of the mevalonate pathway in human cells, be it in metabolically active tissues including tumor cells or through inhibition of farnesyl pyrophosphate synthase by aminobisphophonates such as zoledronate, is thought to render such cells targets of Vc9/Vd2 T cells, despite the absence of the high bioactivity metabolite HMB-PP in this context [11,[16][17][18]. Zoledronate and related drugs are therefore receiving substantial attention as Vc9/Vd2 T cellstimulating agents in vivo especially with respect to immunotherapies against advanced solid and hematological tumors [19][20][21].The recent landmark discovery of butyrophilin 3A (BTN3A/ CD277) as the long-sought unconventional 'presenting' molecule for HMB-PP and IPP provided a molecular mechanism that elegantly integrates the action of endogenous and exogenous stimuli via binding of phosphoantigens to the intracellular B30.2 (PRY-SPRY) domain of BTN3A [22][23][24][25]. This intracellular recognition of HMB-PP and IPP evokes similar cases of B30.2-mediated innate responses through proteins such as TRIM5a and TRIM21 [26,27], thereby adding BTN3A to the rapidly growing number of innate pattern recognition receptors.…”
mentioning
confidence: 99%